2022
DOI: 10.3390/ijerph19042394
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Noise Pollution and Self-Reported Health Status among Adult Population of Bangladesh

Abstract: Despite the public health concern, there is a dearth of research regarding perceived noise pollution and noise-related health status in Bangladesh. This study was carried out to evaluate the noise-related health status among Bangladesh’s adult population. 1386 adult Bangladeshis participated in an online survey. A linear regression model was used to evaluate overall noise-related health status determinants. 91% of the survey population reported noisy environments in their neighborhood, with the majority report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The findings of this study revealed that younger respondents reported the possibility of being affected by sound pollution-related health problems (conversation problems and irregular heartbeat problems) whereas aged respondents were less likely to be affected. Another study found similar findings that young people were highly annoyed by traffic-induced noise and more likely to experience related problems (Rahman et al, 2022). Additionally, another study showed that the aged person reported a variety of problems that were not reported by the respondents of other age groups (Carrier et al, 2016;Singh and Davar, 2017), which is also similar to this study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The findings of this study revealed that younger respondents reported the possibility of being affected by sound pollution-related health problems (conversation problems and irregular heartbeat problems) whereas aged respondents were less likely to be affected. Another study found similar findings that young people were highly annoyed by traffic-induced noise and more likely to experience related problems (Rahman et al, 2022). Additionally, another study showed that the aged person reported a variety of problems that were not reported by the respondents of other age groups (Carrier et al, 2016;Singh and Davar, 2017), which is also similar to this study.…”
Section: Discussionsupporting
confidence: 86%
“…This study found that different types of vehicles on the roadway are the main cause of sound pollution in the study area. An earlier study showed that motor vehicles are the main source of high levels of noise (Aftab et al, 2007;Carrier et al, 2016;Clark and Paunovic, 2018;Hoque et al, 2013;Rahman et al, 2022;Sultana et al, 2020). The uncontrolled traffic across the metropolitan area is responsible for creating sound pollution in Dhaka city (Bint and Rahman, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, noise pollution can cause hearing loss [ 2 ] that may impair the quality of life. Due to the existence of noise pollution, depression, anxiety, stress, and other conditions may also be exacerbated [ 10 , 11 ], thus increasing dissatisfaction with life. Therefore, we propose Hypothesis 1.…”
Section: Methodsmentioning
confidence: 99%
“…Noise pollution has become the second most damaging environmental factor to human health after air pollution [ 7 , 8 ]. Noise pollution can cause sleep disorders, anxiety, depression, aggravation of personal troubles, damage to interpersonal relationships, and other factors related to well-being and life satisfaction [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Undoubtedly, noise pollution threatens people’s health and quality of life.…”
Section: Introductionmentioning
confidence: 99%